High-thermal-conductivity aluminum-based composite copper-clad plate and processing technology thereof

By using alumina of different particle sizes, modified graphene and nitrifying as thermal fillers in the insulating dielectric layer of the aluminum-based composite copper clad plate, and combining with the mixture of resins such as modified epoxy resins to form a mosaic structure and a mesh structure, the problem of insufficient thermal conductivity and peel resistance in the prior art is solved, and the improvement of high thermal conductivity, heat resistance and peel resistance is achieved.

CN119872022AInactive Publication Date: 2025-04-25SHENZHEN XINRONGJIN INSULATION MATERIAL CO LTD

Patent Information

Application Number
CN202510393488.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has failed to improve its thermal conductivity and peel resistance by optimizing the resin component and filler component of the insulating dielectric layer of aluminum-based composite copper clad plate.

Method used

Alumina, modified graphene and boron nitride of different particle sizes are used as thermal fillers to form a damascene structure under sectional hot pressing. Combined with the mixture of modified epoxy resin, phenolic resin, liquid crystal resin and epoxy resin, a mesh structure is formed to improve bonding and mechanical properties.

Benefits of technology

The thermal conductivity, heat resistance and peel resistance of aluminum-based composite copper clad plate are significantly improved, forming excellent thermal conductivity network and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872022A_ABST
    Figure CN119872022A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum substrate production, and particularly relates to a high-thermal-conductivity aluminum-based composite copper-clad plate and a processing technology thereof. Aluminum oxide, modified graphene and boron nitride with different particle sizes are used as heat conduction filler, the heat conduction filler moves to holes of an oxidation layer of the aluminum substrate under segmented hot pressing to form a mosaic structure, the heat conduction performance between the holes is improved, and the content of air in the holes is reduced; modified epoxy resin is prepared from hydrogen-containing silicone oil and vinyl benzyl glycidyl ether, phenyl groups are introduced, the thermal stability of the resin is improved, the heat-resistant insulating resin prepared by mixing the modified epoxy resin, phenolic resin, liquid crystal resin and epoxy resin can form a net structure, and the heat-resistant insulating resin has excellent adhesive property and mechanical property; the curing accelerator prepared by mixing the cross-linking agent and 2-methylimidazole has excellent continuous curing accelerating performance. The prepared aluminum-based composite copper-clad plate has excellent heat conduction, heat resistance and stripping resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum substrate production, and specifically relates to a high thermal conductivity aluminum-based composite copper-clad plate and a processing technology thereof. Background Art

[0002] Aluminum-based copper clad laminate, also known as aluminum substrate, is a substrate material used in printed circuit board manufacturing. With the continuous development of electronic products, the demand for heat dissipation of circuit boards is also increasing. Aluminum-based copper clad laminate has good heat dissipation, strength and rigidity, so it is widely used in high-power electronic devices, LED lighting, power amplifiers and other electronic fields.

[0003] The Chinese invention patent with publication number CN115122721B discloses a high thermal conductivity aluminum-based copper-clad laminate and its preparation method. A high thermal conductivity aluminum-based copper-clad laminate, from bottom to top, comprises: a copper foil layer, an aluminum base layer, and an insulating layer; the surface of the insulating layer is coated with an epoxy resin composition. The raw materials for preparing the epoxy resin composition include: epoxy resin, curing agent, filler, and auxiliary materials. The aluminum-based copper-clad laminate provided by the invention can achieve better thermal conductivity and heat dissipation effects. During use, it can avoid short circuits or failures in its internal circuits. At the same time, it can also increase the service life of the copper-clad laminate, which is more convenient for users to use. However, there is a technical problem in the prior art that the resin component and filler component of the insulating dielectric layer of the aluminum-based composite copper-clad laminate are not further optimized to improve the thermal conductivity and anti-peeling properties of the aluminum-based composite copper-clad laminate. Summary of the invention

[0004] The object of the present invention is to provide a high thermal conductivity aluminum-based composite copper-clad laminate and a processing technology thereof, so as to solve the technical problem that the prior art has not further optimized the resin component and the filler component of the insulating dielectric layer of the aluminum-based composite copper-clad laminate to improve the thermal conductivity and anti-peeling performance of the aluminum-based composite copper-clad laminate.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The high thermal conductivity aluminum-based composite copper-clad laminate is provided with an aluminum substrate layer, an insulating dielectric layer and a copper foil layer in sequence from bottom to top; The material of the aluminum substrate layer is 1050 series aluminum alloy, with a thickness of 1-2 mm; the thickness of the copper foil layer is 18-50 μm.

[0006] The insulating medium layer has a thickness of 70-100 μm and is composed of the following components in parts by mass: 100-200 parts of heat-resistant insulating resin, 60-70 parts of thermal conductive filler, 5-10 parts of high-temperature curing agent, 2-5 parts of curing accelerator and 2-5 parts of toughening aid; The heat-resistant insulating resin consists of 100-120 parts of phenolic resin, 20-30 parts of liquid crystal resin, 20-30 parts of modified epoxy resin and 200-250 parts of epoxy resin.

[0007] The phenolic resin is one or more combinations of BMJ-91, PF-651 and BMJ-93.

[0008] The liquid crystal resin is one or more combinations of E5002L, E6808LHF, and E7006L.

[0009] The epoxy resin is one or more combinations of E21, E44 and E51.

[0010] The high temperature curing agent is one or more combinations of diaminodiphenyl sulfone, metaphenylenediamine, and diaminodiphenylmethane.

[0011] The toughening aid is one or more combinations of nitrile rubber, butyl rubber and carboxyl acrylic rubber.

[0012] The processing technology of high thermal conductivity aluminum-based composite copper clad laminate includes the following steps: S1. Material pretreatment: clean and polish the aluminum substrate and copper foil to remove the oil layer and passivation layer on the surface, and dry them at 160~180℃ for later use; S2. Aluminum substrate roughening treatment: put the dried aluminum substrate as the positive electrode into the electrolyte, pass the current, oxidize at 60-70°C for 60-80 minutes, and electroplate to obtain an oxide layer; S3, preparing an insulating dielectric layer: adding a toughening agent to an organic solvent, standing at 80-90°C for swelling for 1-2 hours, stirring at a speed of 800-900 r / min to obtain a toughening solution, adding the toughening solution, heat-resistant insulating resin, thermal conductive filler and high-temperature curing agent to the organic solvent, mixing, standing for 8-10 hours to remove bubbles, to obtain an insulating adhesive, coating the insulating adhesive on a release film, semi-curing at room temperature, to obtain an insulating dielectric layer; S4, hot pressing bonding: laminating the insulating dielectric layer on the aluminum substrate through a release film, then placing a copper foil for hot pressing and curing, and cooling to room temperature to obtain a crude aluminum-based composite copper-clad laminate; S5. Testing: Cut and trim the rough aluminum-based composite copper-clad laminate, and after testing the strength to be qualified, obtain a high thermal conductivity aluminum-based composite copper-clad laminate.

[0013] Preferably, the thickness of the oxide layer in S2 is 30-50 μm, the oxidation voltage is 30-50 V, and the oxidation current density is 2-5 A / dm 2 .

[0014] Preferably, in S2, 100-150 parts of sulfuric acid, 10-15 parts of citric acid, 3-5 parts of aluminum sulfate and 830-887 parts of deionized water are prepared to obtain an electrolyte, based on mass parts.

[0015] Preferably, the organic solvent in S3 is one or more combinations of acetone, N,N-dimethylformamide and ethanol.

[0016] Preferably, the hot pressing curing in S4 is carried out by uniformly heating the temperature to 150-200°C at a heating rate of 2-4°C, curing for 60-80 min at a pressure of 8-12 MPa, and after detecting that no gas is discharged, uniformly heating the temperature to 220-240°C at a heating rate of 4-5°C, curing for 50-80 min at a pressure of 15-18 MPa.

[0017] Preferably, the method for preparing the heat-resistant insulating resin comprises the following steps: S11. Add 180-200 parts of vinyl benzyl glycidyl ether by mass into a reaction kettle, stir at a speed of 300-500 r / min and heat to 105-110° C., introduce nitrogen and keep warm for 30-40 min, cool to 80-90° C., add 0.1-0.3 parts of chloroplatinic acid, drop 300-350 parts of hydrogen-containing silicone oil into the system, heat to 110-120° C. and react for 5-6 h to obtain a modified epoxy resin; S12. Mix 100-120 parts of phenolic resin, 20-30 parts of liquid crystal resin, 20-30 parts of modified epoxy resin and 200-250 parts of epoxy resin in parts by mass to prepare a heat-resistant insulating resin.

[0018] Preferably, the hydrogen-containing silicone oil in S11 is one or more combinations of RH-H57, RH-H502, and RH-H510.

[0019] Preferably, the synthesis principle of the modified epoxy resin in S11 is as follows:

[0020] The R group is any one of a methyl group, a hydrogen group, and a carbon-containing branched chain of the hydrogen-containing silicone oil.

[0021] Preferably, the method for preparing the thermally conductive filler comprises the following steps: S21, adding 8-10 parts of graphene to a mixed solution of 80-100 parts of acetone and deionized water by mass, adding 1.5-4 parts of nano-spherical aluminum oxide to ethanol to prepare a dispersion and then adding it to the system, adding 0.5-0.8 parts of polyvinyl pyrrolidone, stirring ultrasonically for 30-40 minutes, freeze-drying at 0-5° C., and grinding to obtain modified graphene; S22. Mix 1-3 parts of nano boron nitride, 5-10 parts of modified graphene, 30-40 parts of alumina with an average particle size of 0.1-0.2 μm, 15-20 parts of alumina with an average particle size of 1-2 μm, and 15-20 parts of alumina with an average particle size of 40-50 μm, by mass, to prepare a thermally conductive filler.

[0022] Preferably, the average particle size of the nano-spherical alumina in S21 is 5-10 nm.

[0023] Preferably, in S21, acetone and deionized water are mixed in a volume ratio of 2:1 to obtain a mixed solution.

[0024] Preferably, the average particle size of the nano boron nitride in S22 is 20-30 nm.

[0025] Preferably, the method for preparing the curing accelerator comprises the following steps: S31. Add 3-5 parts of nano-silicon dioxide to a mixed solution of 40-50 parts of ethanol and deionized water by mass, and perform ultrasonic dispersion for 10-20 minutes. Add 0.4-0.5 parts of KH-560 and 0.4-0.5 parts of KH-570 at a speed of 200-300 r / min, raise the temperature to 60-70°C and keep the reaction for 5-6 hours. Dry at 50-60°C and grind to obtain modified silicon dioxide. S32. By mass, 5-6 parts of epoxy resin E21 and 14-15 parts of cresyl glycidyl ether are fully mixed as core material, 5-10 parts of styrene, 3-5 parts of dehydrated glyceryl methacrylate and 0.3-0.5 parts of divinylbenzene are added to 10-20 parts of core material, and ultrasonic dispersion is performed for 20-30 minutes to obtain an oil phase, 1-2 parts of modified silicon dioxide are dissolved in 50-60 parts of deionized water, and ultrasonic dispersion is performed for 20-30 minutes to obtain an aqueous phase, the oil phase and the aqueous phase are mixed, and stirred at a speed of 5000-6000 r / min for 5-10 minutes, and then 0.5-0.7 parts of triethylenetetramine are added at a speed of 200-300 r / min, and stirred for 2-3 minutes. The mixture is reacted at 40-50°C for 5-6 hours, and dried and ground to obtain a cross-linking agent; S33, adding 5 to 10 parts of 2-methylimidazole to 15 to 20 parts of a cross-linking agent, and mixing at a rotation speed of 200 to 300 r / min for 5 to 10 minutes to obtain a curing accelerator.

[0026] Preferably, in S31, ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a mixed solution.

[0027] Preferably, the average particle size of the nano-silicon dioxide in S31 is 5-10 nm.

[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention uses aluminum oxide, modified graphene and boron nitride of different particle sizes as thermal conductive fillers, and moves the thermal conductive fillers to the holes of the oxide layer of the aluminum substrate under segmented hot pressing to form a mosaic structure, thereby improving the thermal conductivity between the holes and reducing the air content in the holes; hydrogen-containing silicone oil and vinyl benzyl glycidyl ether are used to prepare modified epoxy resin, and phenyl groups are introduced to improve the thermal stability of the resin; the heat-resistant insulating resin prepared by mixing the modified epoxy resin, phenolic resin, liquid crystal resin and epoxy resin can form a network structure and has excellent bonding and mechanical properties; the aluminum-based composite copper-clad laminate prepared by the present invention has excellent thermal conductivity, heat resistance and anti-peeling properties.

[0029] 2. The present invention prepares a modified epoxy resin by using hydrogen-containing silicone oil and vinyl benzyl glycidyl ether, introduces a phenyl group, and improves the insulation performance and thermal stability of the resin; the added liquid crystal resin makes the resin present a certain order in the microstructure after curing, which can effectively reduce phonon scattering and improve the thermal conductivity of the resin base; the heat-resistant insulating resin prepared by mixing the modified epoxy resin, phenolic resin, liquid crystal resin and epoxy resin can form a network structure, has excellent bonding properties and mechanical properties, and improves the heat resistance of the insulating medium layer.

[0030] 3. The present invention modifies graphene by nano-spherical alumina, so that the graphene adheres to the nano-spherical alumina to form wrinkles, thereby improving the orientation of the graphene's thermal conductivity in the vertical direction, forming a continuous thermal conduction path, and improving the thermal conductivity efficiency. By mixing alumina, modified graphene and boron nitride of different particle sizes as thermal conductive fillers, they can synergistically build a thermal conductive network in the heat-resistant insulating resin, thereby improving the thermal conductivity of the insulating medium layer.

[0031] 4. The present invention uses epoxy resin E21 and cresyl glycidyl ether as core materials, adds styrene, anhydrous methacrylate and divinylbenzene to prepare an oil phase, adds silane coupling agent modified nano-silica into deionized water to prepare an aqueous phase, and after the oil and water phases are mixed, triethylenetetramine is added to react. The prepared cross-linking agent has a capsule structure, can continuously release triethylenetetramine during the resin heating and curing stage to improve the curing efficiency, and the outer shell has an epoxy structure to improve the compatibility of the cross-linking agent and the resin; the curing accelerator prepared by mixing the cross-linking agent and 2-methylimidazole has excellent continuous curing promotion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 A schematic diagram of the hierarchical structure of the high thermal conductivity aluminum-based composite copper-clad laminate of the present invention is shown; Figure numerals: 1-aluminum substrate layer, 2-insulating medium layer, 3-copper foil layer. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1, see Figure 1 As shown, the high thermal conductivity aluminum-based composite copper-clad laminate of this embodiment is provided with an aluminum substrate layer 1, an insulating medium layer 2 and a copper foil layer 3 in sequence from bottom to top; The material of the aluminum substrate layer is 1050 series aluminum alloy, with a thickness of 1.5 mm; the thickness of the copper foil layer is 34 μm.

[0036] The insulating medium layer has a thickness of 85 μm and is composed of the following components by mass: 100 parts of heat-resistant insulating resin, 60 parts of thermal conductive filler, 10 parts of high-temperature curing agent, 2 parts of curing accelerator and 2 parts of toughening aid; The heat-resistant insulating resin consists of 110 parts of phenolic resin, 25 parts of liquid crystal resin, 25 parts of modified epoxy resin and 200 parts of epoxy resin.

[0037] The phenolic resin is BMJ-91, the liquid crystal resin is E5002L, and the epoxy resin is E21.

[0038] The high temperature curing agent is diaminodiphenyl sulfone.

[0039] The toughening aid is nitrile rubber.

[0040] The processing technology of high thermal conductivity aluminum-based composite copper-clad laminate includes the following steps: S1. Material pretreatment: clean and polish the aluminum substrate and copper foil to remove the oil layer and passivation layer on the surface, and dry them at 160°C for later use; S2. Roughening treatment of aluminum substrate: 130 parts of sulfuric acid, 15 parts of citric acid, 3 parts of aluminum sulfate and 852 parts of deionized water were prepared to obtain an electrolyte. The dried aluminum substrate was placed in the electrolyte as the positive electrode, and current was passed. The oxidation voltage was 30V and the oxidation current density was 3A / dm 2 , oxidized at 60°C for 60 min, and electroplated to obtain an oxide layer with a thickness of 46 μm; S3, preparing an insulating dielectric layer: adding a toughening agent to N, N-dimethylformamide, standing at 80°C for swelling for 2 hours, stirring at a speed of 800 r / min to obtain a toughening solution, adding the toughening solution, heat-resistant insulating resin, thermal conductive filler and high-temperature curing agent to N, N-dimethylformamide, mixing, standing for 8 hours to remove bubbles, to obtain an insulating adhesive, coating the insulating adhesive on a release film, semi-curing at room temperature, to obtain an insulating dielectric layer; S4, hot pressing bonding: the insulating dielectric layer is coated on the aluminum substrate through a release film, and then a copper foil is placed, and the temperature is uniformly increased to 160°C at a heating rate of 2°C, and cured for 60 minutes at a pressure of 8MPa. After detecting that there is no gas discharge, the temperature is uniformly increased to 220°C at a heating rate of 4°C, and cured for 60 minutes at a pressure of 15MPa, and cooled to room temperature to obtain a crude aluminum-based composite copper-clad laminate; S5. Testing: Cut and trim the rough aluminum-based composite copper-clad laminate, and after testing the strength to be qualified, obtain a high thermal conductivity aluminum-based composite copper-clad laminate.

[0041] The method for preparing the heat-resistant insulating resin of this embodiment comprises the following steps: S11, by mass, add 190 parts of vinyl benzyl glycidyl ether into a reaction kettle, stir at a speed of 300 r / min and heat to 110° C., introduce nitrogen and keep warm for 30 min, cool to 80° C., add 0.1 parts of chloroplatinic acid, dropwise add 320 parts of hydrogen-containing silicone oil RH-H57 into the system, heat to 110° C. and react for 6 h to obtain a modified epoxy resin; S12. Mix 110 parts of phenolic resin, 25 parts of liquid crystal resin, 25 parts of modified epoxy resin and 200 parts of epoxy resin by mass to prepare a heat-resistant insulating resin.

[0042] The preparation method of the thermal conductive filler of this embodiment comprises the following steps: S21. Acetone and deionized water are mixed in a volume ratio of 2:1 by mass to obtain a mixed solution, 8 parts of graphene are added to a mixed solution of 80 parts of acetone and deionized water, 2 parts of nano-spherical alumina with an average particle size of 5 nm are added to ethanol to obtain a dispersion, and then added to the system, 0.5 parts of polyvinyl pyrrolidone are added, ultrasonic stirring is performed for 30 minutes, freeze-dried at 0° C., and ground to obtain modified graphene; S22. Mix 3 parts of nano boron nitride with an average particle size of 25 nm, 5 parts of modified graphene, 30 parts of aluminum oxide with an average particle size of 0.2 μm, 20 parts of aluminum oxide with an average particle size of 1 μm and 15 parts of aluminum oxide with an average particle size of 50 μm, by mass, to prepare a thermally conductive filler.

[0043] The preparation method of the curing accelerator of this embodiment comprises the following steps: S31. According to parts by mass, ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a mixed solution, 5 parts of nano-silicon dioxide are added to the mixed solution of 50 parts of ethanol and deionized water, ultrasonically dispersed for 20 minutes, 0.4 parts of KH-560 and 0.4 parts of KH-570 are added at a speed of 200 r / min, the temperature is raised to 60°C and the reaction is kept for 5 hours, and the mixture is dried at 60°C and ground to obtain modified silicon dioxide; S32. By mass, 6 parts of epoxy resin E21 and 14 parts of cresyl glycidyl ether were mixed thoroughly as core material, 5 parts of styrene, 5 parts of dehydrated glyceryl methacrylate and 0.3 parts of divinylbenzene were added to 15 parts of core material, and ultrasonic dispersion was performed for 20 minutes to obtain an oil phase, 2 parts of modified silicon dioxide were dissolved in 50 parts of deionized water, and ultrasonic dispersion was performed for 20 minutes to obtain an aqueous phase, the oil phase and the aqueous phase were mixed, and stirred at a speed of 5000 r / min for 5 minutes, and then 0.5 parts of triethylenetetramine were added at a speed of 200 r / min, and stirred for 2 minutes. The mixture was reacted at 40°C for 5 hours, and dried and ground to obtain a cross-linking agent; S33, adding 5 parts of 2-methylimidazole to 15 parts of the cross-linking agent, mixing at a rotation speed of 200 r / min for 5 minutes, to obtain a curing accelerator.

[0044] Example 2, see Figure 1 As shown, the high thermal conductivity aluminum-based composite copper-clad laminate of this embodiment is provided with an aluminum substrate layer, an insulating medium layer and a copper foil layer in sequence from bottom to top; The material of the aluminum substrate layer is 1050 series aluminum alloy, with a thickness of 1.1 mm; the thickness of the copper foil layer is 24 μm.

[0045] The insulating medium layer has a thickness of 73 μm and is composed of the following components by mass: 100 parts of heat-resistant insulating resin, 60 parts of thermal conductive filler, 5 parts of high-temperature curing agent, 3 parts of curing accelerator and 3 parts of toughening aid; The heat-resistant insulating resin consists of 100 parts of phenolic resin, 20 parts of liquid crystal resin, 20 parts of modified epoxy resin and 200 parts of epoxy resin.

[0046] The phenolic resin is PF-651, the liquid crystal resin is E6808LHF, and the epoxy resin is E44.

[0047] The high temperature curing agent is m-phenylenediamine.

[0048] The toughening aid is butyl rubber.

[0049] The processing technology of high thermal conductivity aluminum-based composite copper clad laminate includes the following steps: S1. Material pretreatment: clean and polish the aluminum substrate and copper foil to remove the oil layer and passivation layer on the surface, and dry them at 170°C for later use; S2. Roughening treatment of aluminum substrate: 100 parts of sulfuric acid, 10 parts of citric acid, 3 parts of aluminum sulfate and 887 parts of deionized water are prepared to obtain an electrolyte. The dried aluminum substrate is placed in the electrolyte as the positive electrode, and current is passed. The oxidation voltage is 50V and the oxidation current density is 5A / dm 2 , oxidized at 70°C for 60 min, and electroplated to obtain an oxide layer with a thickness of 33 μm; S3, preparing an insulating dielectric layer: adding a toughening agent to acetone, standing at 90°C for 1 hour to swell, stirring at a speed of 800 r / min to obtain a toughening solution, adding the toughening solution, heat-resistant insulating resin, thermal conductive filler and high-temperature curing agent to acetone, mixing, standing for 9 hours to remove bubbles, to obtain an insulating adhesive solution, coating the insulating adhesive solution on a release film, semi-curing at room temperature, to obtain an insulating dielectric layer; S4, hot pressing bonding: the insulating dielectric layer is coated on the aluminum substrate through a release film, and then a copper foil is placed, and the temperature is uniformly increased to 170°C at a heating rate of 3°C, and cured for 70 minutes at a pressure of 10MPa. After detecting that there is no gas discharge, the temperature is uniformly increased to 240°C at a heating rate of 5°C, and cured for 80 minutes at a pressure of 16MPa, and cooled to room temperature to obtain a crude aluminum-based composite copper-clad laminate; S5. Testing: Cut and trim the rough aluminum-based composite copper-clad laminate, and after testing the strength to be qualified, obtain a high thermal conductivity aluminum-based composite copper-clad laminate.

[0050] The difference between the heat-resistant insulating resin of this embodiment and that of Embodiment 1 is that the type of hydrogen-containing silicone oil is replaced with RH-H510.

[0051] The preparation method of the thermal conductive filler and the curing accelerator of this embodiment is the same as the preparation method of embodiment 1.

[0052] Example 3, see Figure 1 As shown, the high thermal conductivity aluminum-based composite copper-clad laminate of this embodiment is provided with an aluminum substrate layer, an insulating medium layer and a copper foil layer in sequence from bottom to top; The material of the aluminum substrate layer is 1050 series aluminum alloy, with a thickness of 1.8 mm; the thickness of the copper foil layer is 45 μm.

[0053] The insulating medium layer has a thickness of 100 μm and is composed of the following components by mass: 200 parts of heat-resistant insulating resin, 70 parts of thermal conductive filler, 10 parts of high-temperature curing agent, 5 parts of curing accelerator and 5 parts of toughening aid; The heat-resistant insulating resin consists of 120 parts of phenolic resin, 30 parts of liquid crystal resin, 30 parts of modified epoxy resin and 250 parts of epoxy resin.

[0054] The phenolic resin is BMJ-93, the liquid crystal resin is E7006L, and the epoxy resin is E51.

[0055] The high temperature curing agent is diaminodiphenylmethane.

[0056] The toughening aid is carboxyl acrylic rubber.

[0057] The processing technology of high thermal conductivity aluminum-based composite copper-clad laminate includes the following steps: S1. Material pretreatment: clean and polish the aluminum substrate and copper foil to remove the oil layer and passivation layer on the surface, and dry them at 180°C for later use; S2. Aluminum substrate roughening treatment: 150 parts of sulfuric acid, 15 parts of citric acid, 5 parts of aluminum sulfate and 830 parts of deionized water were prepared to obtain an electrolyte. The dried aluminum substrate was placed in the electrolyte as the positive electrode, and current was passed. The oxidation voltage was 40V and the oxidation current density was 4A / dm 2 , oxidized at 70°C for 80 min, and electroplated to obtain an oxide layer with a thickness of 50 μm; S3, preparing an insulating dielectric layer: adding a toughening agent to ethanol, standing at 90°C for swelling for 2 hours, stirring at a speed of 900 r / min to obtain a toughening solution, adding the toughening solution, heat-resistant insulating resin, thermal conductive filler and high-temperature curing agent to ethanol, mixing, standing for 10 hours to remove bubbles, to obtain an insulating adhesive, coating the insulating adhesive on a release film, semi-curing at room temperature, to obtain an insulating dielectric layer; S4, hot pressing bonding: the insulating dielectric layer is coated on the aluminum substrate through a release film, and then a copper foil is placed, and the temperature is uniformly increased to 200°C at a heating rate of 4°C, and cured for 80 minutes at a pressure of 12MPa. After detecting that there is no gas discharge, the temperature is uniformly increased to 240°C at a heating rate of 4°C, and cured for 80 minutes at a pressure of 18MPa, and cooled to room temperature to obtain a crude aluminum-based composite copper-clad laminate; S5. Testing: Cut and trim the rough aluminum-based composite copper-clad laminate, and after testing the strength to be qualified, obtain a high thermal conductivity aluminum-based composite copper-clad laminate.

[0058] The difference between the thermally conductive filler of this embodiment and that of Embodiment 1 is that the composition of the thermally conductive filler is replaced by 3 parts of nano-boron nitride with an average particle size of 30 nm, 10 parts of modified graphene, 40 parts of aluminum oxide with an average particle size of 0.2 μm, 20 parts of aluminum oxide with an average particle size of 2 μm and 20 parts of aluminum oxide with an average particle size of 50 μm.

[0059] The preparation method of the heat-resistant insulating resin and the curing accelerator of this embodiment is the same as the preparation method of embodiment 1.

[0060] Comparative Example 1: The difference between the high thermal conductivity aluminum-based composite copper-clad laminate in this comparative example and Example 1 is that the heat-resistant insulating resin is replaced by only epoxy resin.

[0061] Comparative Example 2: The difference between the high thermal conductivity aluminum-based composite copper-clad laminate in this comparative example and Example 1 is that the thermal conductive filler is replaced by aluminum oxide with an average particle size of only 2 μm.

[0062] Comparative Example 3: The difference between the high thermal conductivity aluminum-based composite copper-clad laminate in this comparative example and Example 1 is that the curing accelerator is replaced with only 2-methylimidazole.

[0063] Performance Testing According to the IPC-TM-650 2.4.8 test standard, the peel strength of the composite copper clad laminates prepared in each embodiment and comparative example was measured.

[0064] According to the IPC TM-650 2.5.6 test standard, the breakdown voltage of the composite copper clad laminates prepared in each embodiment and comparative example was measured.

[0065] The thermal conductivity of the composite copper clad laminates prepared in each embodiment and comparative example was measured according to ASTM D5470 test standard.

[0066] The test results are shown in Table 1: Table 1 Performance test Serial number Peel strength (N / mm) Breakdown voltage (kV) <![CDATA[Thermal conductivity (W·m -1 ·k -1 ).]]> Example 1 1.75 5.71 2.69 Example 2 1.76 5.73 2.64 Example 3 1.81 5.78 2.58 Comparative Example 1 1.48 5.59 1.59 Comparative Example 2 1.65 5.70 1.46 Comparative Example 3 1.43 5.65 2.56 It can be seen from the data in Table 1 that the peel strength of the high thermal conductivity aluminum-based composite copper-clad laminates prepared in Examples 1 to 3 is 1.75 to 1.81 N / mm, and the breakdown voltage is 5.71 to 5.78 kV, indicating that the high thermal conductivity aluminum-based composite copper-clad laminates prepared in the present invention have excellent anti-peeling and insulation properties; the thermal conductivity of the high thermal conductivity aluminum-based composite copper-clad laminates prepared in Examples 1 to 3 is 2.58 to 2.69 W·m -1 ·k -1 The thermal conductive filler in Comparative Example 2 is replaced with aluminum oxide with an average particle size of only 2 μm. The thermal conductive filler cannot be filled into the holes of the oxide layer of the aluminum substrate to form a mosaic structure, resulting in the thermal conductive network of the oxide layer being unable to efficiently transfer heat. Therefore, its thermal conductivity is only 21.46 W·m -1 ·k -1, indicating that the high thermal conductivity aluminum-based composite copper-clad laminate prepared by the present invention has excellent thermal conductivity.

[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0068] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. High thermal conductivity aluminum-based composite copper-clad laminate, characterized in that: An aluminum substrate layer, an insulating dielectric layer, and a copper foil layer are sequentially arranged from bottom to top; The material of the aluminum substrate layer is 1050 series aluminum alloy, with a thickness of 1-2 mm; the thickness of the copper foil layer is 18-50 μm; The insulating medium layer has a thickness of 70-100 μm and is composed of the following components in parts by mass: 100-200 parts of heat-resistant insulating resin, 60-70 parts of thermal conductive filler, 5-10 parts of high-temperature curing agent, 2-5 parts of curing accelerator and 2-5 parts of toughening aid; The heat-resistant insulating resin is composed of the following components in parts by mass: 100-120 parts of phenolic resin, 20-30 parts of liquid crystal resin, 20-30 parts of modified epoxy resin and 200-250 parts of epoxy resin.

2. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 1, characterized in that: The phenolic resin is one or more combinations of BMJ-91, PF-651, and BMJ-93; the liquid crystal resin is one or more combinations of E5002L, E6808LHF, and E7006L; the epoxy resin is one or more combinations of E21, E44, and E51; the high-temperature curing agent is one or more combinations of diaminodiphenyl sulfone, metaphenylenediamine, and diaminodiphenylmethane; the toughening aid is one or more combinations of nitrile rubber, butyl rubber, and carboxyl acrylic rubber.

3. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 1, characterized in that: The preparation method of the heat-resistant insulating resin comprises the following steps: S11. Add 180-200 parts of vinyl benzyl glycidyl ether by mass into a reaction kettle, stir at a speed of 300-500 r / min and heat to 105-110° C., introduce nitrogen and keep warm for 30-40 min, cool to 80-90° C., add 0.1-0.3 parts of chloroplatinic acid, drop 300-350 parts of hydrogen-containing silicone oil into the system, heat to 110-120° C. and react for 5-6 h to obtain a modified epoxy resin; S12. Mix 100-120 parts of phenolic resin, 20-30 parts of liquid crystal resin, 20-30 parts of modified epoxy resin and 200-250 parts of epoxy resin in parts by mass to prepare a heat-resistant insulating resin.

4. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 3, characterized in that: The hydrogen-containing silicone oil in S11 is one or more combinations of RH-H57, RH-H502, and RH-H510.

5. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 1, characterized in that: The preparation method of the thermal conductive filler comprises the following steps: S21, adding 8-10 parts of graphene to a mixed solution of 80-100 parts of acetone and deionized water by mass, adding 1.5-4 parts of nano-spherical aluminum oxide to ethanol to prepare a dispersion and then adding it to the system, adding 0.5-0.8 parts of polyvinyl pyrrolidone, stirring ultrasonically for 30-40 minutes, freeze-drying at 0-5° C., and grinding to obtain modified graphene; S22. Mix 1-3 parts of nano boron nitride, 5-10 parts of modified graphene, 30-40 parts of alumina with an average particle size of 0.1-0.2 μm, 15-20 parts of alumina with an average particle size of 1-2 μm, and 15-20 parts of alumina with an average particle size of 40-50 μm, by mass, to prepare a thermally conductive filler.

6. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 5, characterized in that: The average particle size of the nano-spherical aluminum oxide in S21 is 5-10 nm, and acetone and deionized water are mixed in a volume ratio of 2:1 to obtain a mixed solution; the average particle size of the nano-boron nitride in S22 is 20-30 nm.

7. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 1, characterized in that: The preparation method of the curing accelerator comprises the following steps: S31. Add 3-5 parts of nano-silicon dioxide to a mixed solution of 40-50 parts of ethanol and deionized water by mass, and perform ultrasonic dispersion for 10-20 minutes. Add 0.4-0.5 parts of KH-560 and 0.4-0.5 parts of KH-570 at a speed of 200-300 r / min, raise the temperature to 60-70°C and keep the reaction for 5-6 hours. Dry at 50-60°C and grind to obtain modified silicon dioxide. S32. By mass, 5-6 parts of epoxy resin E21 and 14-15 parts of cresyl glycidyl ether are fully mixed as core material, 5-10 parts of styrene, 3-5 parts of dehydrated glyceryl methacrylate and 0.3-0.5 parts of divinylbenzene are added to 10-20 parts of core material, and ultrasonic dispersion is performed for 20-30 minutes to obtain an oil phase, 1-2 parts of modified silicon dioxide are dissolved in 50-60 parts of deionized water, and ultrasonic dispersion is performed for 20-30 minutes to obtain an aqueous phase, the oil phase and the aqueous phase are mixed, and stirred at a speed of 5000-6000 r / min for 5-10 minutes, and then 0.5-0.7 parts of triethylenetetramine are added at a speed of 200-300 r / min, and stirred for 2-3 minutes. The mixture is reacted at 40-50°C for 5-6 hours, and dried and ground to obtain a cross-linking agent; S33, adding 5 to 10 parts of 2-methylimidazole to 15 to 20 parts of a cross-linking agent, and mixing at a rotation speed of 200 to 300 r / min for 5 to 10 minutes to obtain a curing accelerator.

8. The high thermal conductivity aluminum-based composite copper-clad laminate according to claim 7, characterized in that: In the S31, ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a mixed solution, and the average particle size of the nano-silicon dioxide is 5-10 nm.

9. The processing technology of high thermal conductivity aluminum-based composite copper-clad laminate is characterized in that: The steps include: S1. Material pretreatment: clean and polish the aluminum substrate and copper foil to remove the oil layer and passivation layer on the surface, and dry them at 160~180℃ for later use; S2. Aluminum substrate roughening treatment: put the dried aluminum substrate as the positive electrode into the electrolyte, pass the current, oxidize at 60-70°C for 60-80 minutes, and electroplate to obtain an oxide layer; S3, preparing an insulating dielectric layer: adding a toughening agent to an organic solvent, standing at 80-90°C for swelling for 1-2 hours, stirring at a speed of 800-900 r / min to obtain a toughening solution, adding the toughening solution, heat-resistant insulating resin, thermal conductive filler and high-temperature curing agent to the organic solvent, mixing, standing for 8-10 hours to remove bubbles, to obtain an insulating adhesive, coating the insulating adhesive on a release film, semi-curing at room temperature, to obtain an insulating dielectric layer; S4, hot pressing bonding: laminating the insulating dielectric layer on the aluminum substrate through a release film, then placing a copper foil for hot pressing and curing, and cooling to room temperature to obtain a crude aluminum-based composite copper-clad laminate; S5. Testing: Cut and trim the rough aluminum-based composite copper-clad laminate, and after testing the strength to be qualified, obtain a high thermal conductivity aluminum-based composite copper-clad laminate.

10. The processing technology of the high thermal conductivity aluminum-based composite copper-clad laminate according to claim 9, characterized in that: The thickness of the oxide layer in S2 is 30-50 μm, the oxidation voltage is 30-50 V, and the oxidation current density is 2-5 A / dm 2 , by mass, 100-150 parts of sulfuric acid, 10-15 parts of citric acid, 3-5 parts of aluminum sulfate and 830-887 parts of deionized water are prepared to obtain an electrolyte; the organic solvent in S3 is one or more combinations of acetone, N,N-dimethylformamide, and ethanol; in S4, the hot pressing curing is uniformly heated to 150-200°C at a heating rate of 2-4°C, and cured for 60-80 minutes at a pressure of 8-12MPa. After detecting that no gas is discharged, the temperature is uniformly increased to 220-240°C at a heating rate of 4-5°C, and cured for 50-80 minutes at a pressure of 15-18MPa.

Citation Information

Patent Citations

  • A high thermal conductivity aluminum-based copper clad laminate and its preparation method

    CN115122721B

  • Thermosetting resin composition, prepreg containing same, laminated board and printed circuit board

    CN105419237A

  • High-frequency heat-conducting substrate and preparation method thereof

    CN111844951A

  • Surface modified epoxy group self-repairing microcapsule as well as preparation method and application thereof

    CN116814111A

  • Preparation method of modified spherical alumina / fold structure graphene / polysiloxane composite heat conduction interface material

    CN118126525A

Cited By

  • Metal-based circuit board and metal-based circuit board manufacturing method

    CN121985473A